Functional phenotype of synovial monocytes modulating inflammatory T-cell responses in rheumatoid arthritis (RA). - Bo Ruem Yoon (Public Library of Science (PLoS), 2014)
Monocytes function as crucial innate effectors in the pathogenesis of chronic inflammatory diseases, including autoimmunity, as well as in the inflammatory response against infectious pathogens. Human monocytes are heterogeneous and can be classified into three distinct subsets based on CD14 and CD16 expression. Although accumulating evidence suggests distinct functions of monocyte subsets in inflammatory conditions, their pathogenic roles in autoimmune diseases remain unclear. Thus, we investigated the phenotypic and functional characteristics of monocytes derived from synovial fluid and peripheral blood in RA patients in order to explore the pathogenic roles of these cells. In RA patients, CD14+CD16+, but not CD14dimCD16+, monocytes are predominantly expanded in synovial fluid and, to a lesser degree, in peripheral blood. Expression of co-signaling molecules of the B7 family, specifically CD80 and CD276, was markedly elevated on synovial monocytes, while peripheral monocytes of RA and healthy controls did not express these molecules without stimulation. To explore how synovial monocytes might gain these unique properties in the inflammatory milieu of the synovial fluid, peripheral monocytes were exposed to various stimuli. CD16 expression on CD14+ monocytes was clearly induced by TGF-β, although co-treatment with IL-1β, TNF-α, or IL-6 did not result in any additive effects. In contrast, TLR stimulation with LPS or zymosan significantly downregulated CD16 expression such that the CD14+CD16+ monocyte subset could not be identified. Furthermore, treatment of monocytes with IFN-γ resulted in the induction of CD80 and HLA-DR expression even in the presence of TGF-β. An in vitro assay clearly showed that synovial monocytes possess the unique capability to promote Th1 as well as Th17 responses of autologous peripheral CD4 memory T cells. Our findings suggest that the cytokine milieu of the synovial fluid shapes the unique features of synovial monocytes as well as their cardinal role in shaping inflammatory T-cell responses in RA.